IMPLEMENTASI PRINSIP PENGEMBANGAN KURIKULUM MERDEKA DALAM PEMBELAJARAN BERBASIS TEKNOLOGI DI SEKOLAH DASAR - Sofyan Iskandar; Deli Setiasari; Handayani, Isna; Putri Anandika Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the principles of the Merdeka Curriculum development in technology-based learning at the elementary school level. The Merdeka Curriculum emphasizes principles such as flexibility, relevance, efficiency, continuity, and active student participation. Using a descriptive qualitative approach, data were obtained through interviews with teachers and literature studies. The results show that teachers have the freedom to design learning activities according to local context and student characteristics, and they can utilize technology adaptively despite limited facilities. Collaborative and creative strategies are applied to overcome infrastructure challenges. Technology-based learning enhances student engagement through independent information exploration, discussions, and presentations. Thus, the principles of the Merdeka Curriculum can be effectively implemented in elementary schools through the support of adaptive and innovative teachers.